2020
DOI: 10.1186/s40813-020-00176-w
|View full text |Cite
|
Sign up to set email alerts
|

A bio-economic simulation study on the association between key performance indicators and pluck lesions in Irish farrow-to-finish pig farms

Abstract: Background Pluck lesions are associated with decreased performance in grower-finisher pigs, but their economic impact needs to be further investigated. This study aimed to identify the main pluck lesions and the cut-off value for their prevalence, associated with changes in average daily gain (ADG) during the wean-to-finish period, to simulate their effects on economic performance of farrow-to-finish farms. Pigs (n = 162 ± 51.9 per farm) from 56 farrow-to-finish farms were inspected at slaughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Overall, the most frequently used cost components were veterinary costs (49/58 studies), feed costs (39/58), and labour costs (26/58); whereas the most frequently used revenue components were reduced carcass value (24/58), fewer growing pigs sold (19/58) and fewer piglets weaned/sold (19/58). The modelling studies that considered the most cost components [ 33 , 36 , 37 , 39 ] all reported that feed costs and the reduced revenue from fewer sold piglets or fattening pigs were the costliest components. Although most studies included these components, 19 out of the 58 studies did not consider feed costs, and 24 did not calculate lost revenues due to fewer piglets weaned or fattening pigs sold.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the most frequently used cost components were veterinary costs (49/58 studies), feed costs (39/58), and labour costs (26/58); whereas the most frequently used revenue components were reduced carcass value (24/58), fewer growing pigs sold (19/58) and fewer piglets weaned/sold (19/58). The modelling studies that considered the most cost components [ 33 , 36 , 37 , 39 ] all reported that feed costs and the reduced revenue from fewer sold piglets or fattening pigs were the costliest components. Although most studies included these components, 19 out of the 58 studies did not consider feed costs, and 24 did not calculate lost revenues due to fewer piglets weaned or fattening pigs sold.…”
Section: Resultsmentioning
confidence: 99%
“…Ferraz et al [ 71 ] estimated a cost of US$6.6 (approximately €6.4) per pig produced considering a reduction in ADG of 27 g associated with lesions (CVPC and pleurisy) in ≥ 15% of the lungs compared with pigs without lesions. Calderón Díaz et al [ 81 ] showed, using a bio-economic simulation study, that from six recorded pluck lesions, pleurisy and lung scars were the main lesions associated with decreases in ADG during the grow-finisher period and a lower economic return.…”
Section: Impact Of Cvpc and Pleurisy On Performancementioning
confidence: 99%
“…Porcine respiratory disease complex (PRDC) is a chronic respiratory disease mainly affecting growing and finishing pigs, causing major economic losses in the pig industry worldwide [ 1 , 2 ]. Generally, the prevalence of respiratory disease ranges from 19% to 74% in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…M. hyopneumoniae is the primary etiological agent of enzootic pneumonia (EP) and plays an important role in PRDC [ 8 , 9 , 10 , 15 , 16 , 17 ]. Despite all efforts made to reduce economic losses caused by this pathogen, M. hyopneumoniae continues to be an important concern for swine herds worldwide [ 1 , 2 , 8 , 9 , 10 , 15 , 16 , 17 ]. In addition to having a negative effect on pig health, animals with CVPC affecting more than 10% of the lung area have a lower average daily weight gain (ADWG) (6 to 9.3%) during the fattening period and a higher feed conversion ratio (0.16 units) [ 1 , 2 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation